2022
DOI: 10.3389/fnagi.2022.795764
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Loneliness, Episodic Memory and Hippocampal Volume Change in Young and Healthy Older Adults: A Longitudinal European Multicenter Study

Abstract: BackgroundLoneliness is most prevalent during adolescence and late life and has been associated with mental health disorders as well as with cognitive decline during aging. Associations between longitudinal measures of loneliness and verbal episodic memory and brain structure should thus be investigated.MethodsWe sought to determine associations between loneliness and verbal episodic memory as well as loneliness and hippocampal volume trajectories across three longitudinal cohorts within the Lifebrain Consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…Our results showing an inverse association between loneliness and cognitive function are consistent with those of previous studies that found loneliness to be a risk factor for cognitive impairment [8,42]. However, several previous studies have failed to find a significant association between loneliness and cognitive function [9,18]; this difference may be related to the measurements used. In those studies, cognitive function was measured using the Mini-Mental State Examination [9], which is less sensitive than the MoCA in measuring the subtle cognitive decline in older people without dementia [43,44], or loneliness was measured using a single item [18], which Abbreviations: CI: confidence interval; Q: quartile a Adjusted for age, sex (male or female), education level (elementary or lower, junior high, senior high, college or higher), current smoking (yes or no), current drinking (yes or no), sitting (h/d), walking for more than 10 min at least one day in the last week (yes or no), moderate or vigorous activity (yes or no), marital status (married or widowed, divorced, or unmarried), living status (living alone, living with one roommate, living with two roommates, living with three roommates), overweight (yes or no), number of comorbidities, hearing impairments (yes or no) is prone to measurement error [45].…”
Section: Inverse Association Between Loneliness and Its Components An...supporting
confidence: 92%
See 3 more Smart Citations
“…Our results showing an inverse association between loneliness and cognitive function are consistent with those of previous studies that found loneliness to be a risk factor for cognitive impairment [8,42]. However, several previous studies have failed to find a significant association between loneliness and cognitive function [9,18]; this difference may be related to the measurements used. In those studies, cognitive function was measured using the Mini-Mental State Examination [9], which is less sensitive than the MoCA in measuring the subtle cognitive decline in older people without dementia [43,44], or loneliness was measured using a single item [18], which Abbreviations: CI: confidence interval; Q: quartile a Adjusted for age, sex (male or female), education level (elementary or lower, junior high, senior high, college or higher), current smoking (yes or no), current drinking (yes or no), sitting (h/d), walking for more than 10 min at least one day in the last week (yes or no), moderate or vigorous activity (yes or no), marital status (married or widowed, divorced, or unmarried), living status (living alone, living with one roommate, living with two roommates, living with three roommates), overweight (yes or no), number of comorbidities, hearing impairments (yes or no) is prone to measurement error [45].…”
Section: Inverse Association Between Loneliness and Its Components An...supporting
confidence: 92%
“…Our results showing an inverse association between loneliness and cognitive function are consistent with those of previous studies that found loneliness to be a risk factor for cognitive impairment [ 8 , 42 ]. However, several previous studies have failed to find a significant association between loneliness and cognitive function [ 9 , 18 ]; this difference may be related to the measurements used. In those studies, cognitive function was measured using the Mini-Mental State Examination [ 9 ], which is less sensitive than the MoCA in measuring the subtle cognitive decline in older people without dementia [ 43 , 44 ], or loneliness was measured using a single item [ 18 ], which is prone to measurement error [ 45 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This has several disadvantages 2 and leads to a bias to exclude individuals that will develop cognitive symptoms early on 31 . Interestingly, human studies utilizing a longitudinal design 17 , 33 , 34 show a rather limited effect of sex on human brain aging.…”
Section: Discussionmentioning
confidence: 99%